2023
DOI: 10.1186/s12913-023-09306-w
|View full text |Cite
|
Sign up to set email alerts
|

Improving heart failure care with an Experience-Based Co-Design approach: what matters to persons with heart failure and their family members?

Abstract: Background Heart failure is a chronic heart condition. Persons with heart failure often have limited physical capability, cognitive impairments, and low health literacy. These challenges can be barriers to healthcare service co-design with family members and professionals. Experience-Based Co-Design is a participatory healthcare quality improvement approach drawing on patients’, family members’ and professionals’ experiences to improve healthcare. The overall aim of this study was to use Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 64 publications
(79 reference statements)
1
3
0
Order By: Relevance
“…27,28 The patients also discussed the importance of both family and peer social support; similar to other research, they indicated how critical family support was but how social support networks were often lacking. 27,28 The patients and caregiver felt that virtual support groups or recordings of other patients should be leveraged to build comradery, provide an opportunity to ask questions, and learn about others' experiences with HF. The patients and caregiver also spent much of the conversation discussing the challenges in managing dietary restrictions, both for HF but also in tandem with those of other chronic conditions.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…27,28 The patients also discussed the importance of both family and peer social support; similar to other research, they indicated how critical family support was but how social support networks were often lacking. 27,28 The patients and caregiver felt that virtual support groups or recordings of other patients should be leveraged to build comradery, provide an opportunity to ask questions, and learn about others' experiences with HF. The patients and caregiver also spent much of the conversation discussing the challenges in managing dietary restrictions, both for HF but also in tandem with those of other chronic conditions.…”
Section: Discussionsupporting
confidence: 53%
“…The patients also discussed how important it was for them to regain their independence and quality of life, but as a motivator to GDMT uptake. Other research has noted that patients with HF and family members often struggle with poor quality of life and that patients have a difficult time with the loss of independence and need to rely on others 27,28 . The patients also discussed the importance of both family and peer social support; similar to other research, they indicated how critical family support was but how social support networks were often lacking 27,28 .…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Four videos were developed based on the experience-based co-design model, an approach that engages caregivers and health care staff in partnership to develop and improve care 14 . Using this model, which has been adopted in other care settings, 15-17 the research team brought Black family caregivers who received hospice care and hospice staff together to share their experiences and identify common priorities. The first phase in the development of the story-based video topics consisted of conducting small group discussions with bereaved Black caregivers who received hospice care 9 .…”
Section: Methodsmentioning
confidence: 99%